Market Segmentation, Targeting, And Positioning Strategy For An Innovative Sustainable Product: A Case Study Of Poreblock By Reservoair - Irfani, Rifdah (Journal Integration of Management Studies, 2026)
The escalating frequency of urban flooding necessitates the adoption of sustainable infrastructure innovations, such as permeable pavements (Poreblock). However, commercialization within Business-to-Business (B2B) construction markets remains stagnant due to the complex dynamics of multipolar Decision-Making Units (DMUs), cost sensitivity, and high epistemic thresholds. This study aims to develop an evidence-based Segmentation, Targeting, and Positioning (STP) strategy for sustainable materials in Indonesia. Employing a mixed-methods design, quantitative data from construction professionals were analyzed using Exploratory Factor Analysis (EFA) and K-Means Clustering, complemented by qualitative stakeholder interviews. The analysis identified three distinct behavioral segments: Performance-Oriented Decision Makers (gatekeeping architects with rigorous empirical demands), Sustainability-Driven Project Implementers (the primary target, pragmatically driven by green-building compliance), and Balanced Urban Developers (a bureaucracy-bound majority). The findings reveal that organizational governance and project compliance mandates are significantly stronger predictors of adoption readiness than traditional occupational demographics. To overcome the substantial upfront price premium of sustainable materials, this study recommends a positioning pivot from generic environmental messaging to Life-Cycle Costing (LCC) and Total Cost of Ownership (TCO). This research contributes to B2B marketing and Diffusion of Innovation literature by empirically contextualizing behavioral segmentation within project-based, risk-averse purchasing ecosystems.